Konserwatyzm szlachecki w dobie oświecenia z perspektywy współczesnych postaci polskiego tradycjonalizmu - Magryś, Roman (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The contemporary research on the Stanislaus epoch expresses the opinion that the crucial civilization proces of the times was the development of the Enlightenment social formation as well as superseding Sarmatism from national life. Still there are more and more views that the Enlightenment was not a dominant cultural factor in Poland, in the late 18th century. The article “Konserwatyzm szlachecki w dobie oświecenia z perspektywy współczesnych postaci polskiego tradycjonalizmu” (“The Conservatism of Nobles in the Enlightenment Period as Viewed by Present-day Figures of Polish Traditionalism”) does not egree with the opinion expressed by Janusz Maciejewski that some Englghtenment values and Sarmatism accept not go hand in hand in people`s mind from the Stanislaus epoch. According to its author, some Sarmatians accept the Enlightenment ideas, witch does not eliminate traditionalism from their minds, but makes it more modern in some way. There is some analogy between the Enlightenment and the present Times. The presenty-day Polish political scene shows that it is possible to joins conservatism with modernism, apology of the past and facing new challenges.
Keywords: conservatism; crucial civilizatio; sarmatism; traditionalizsm